Anger Management Berbasis Spiritual Care dalam Meningkatkan Regulasi Emosi Caregiver Klien Skizofrenia: A Systematic Review - Maulidiyah Junnatul Azizah Heru; Rizki Fitryasari; Hendy Muagiri Margono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Caregivers of schizophrenic clients are faced with various problems and caregiving burdens that can trigger stress and anger. Objective: To determine the effectiveness of spiritual-based anger management interventions in improving the emotional regulation of caregiver clients with schizophrenia. Methods: The sources of the articles used were obtained from searches through the Scopus database, Science Direct, and Proquest. The search for articles is limited from 2015 to 2020. After the articles are obtained, they are then reviewed until the stage of making a systematic review. The keywords used in the article search were “anger management”"spiritual care", "Emotional Regulation" "Caregiver". This systematic review uses 25 articles that fit the inclusion criteria. Results: The spiritual-based anger management interventions from the reviewed research is very significant in increasing the emotional regulation of the caregiver in schizophrenic clients. Conclusion: A spiritual-based anger management strategy can increase emotional regulation and calm attitude so that it will have a good impact on the recovery process for schizophrenic clients. Keywords: anger management; spiritual care; emotion regulation; caregiver; schizophreric ABSTRAK Latar Belakang: Caregiver klien skizofrenia dihadapkan pada berbagai persoalan dan beban pengasuhan yang dapat memicu stress dan kemarahan. Tujuan: untuk mengetahui efektifitas anger management berbasis spiritual dalam meningkatkan regulasi emosi caregiver klien skizofrenia. Metode: Sumber artikel yang digunakan didapat dari pencarian melalui database Scopus, Science Direct dan Proquest. Pencarian artikel dibatasi mulai tahun 2015-2020. Setelah artikel didapatkan, kemudian dilakukan telaah artikel sampai tahap pembuatan systematic review. Kata kunci yang digunakan pada pencarian artikel adalah “anger management” “spiritual care” “Regulasi Emosi” “Caregiver”. Systematic review ini menggunakan 25 artikel yang sesuai dengan kriteria inklusi Hasil: Intervensi anger management berbasis spiritual dari penelitian yang direview sangat singnifikan dalam meningkatkan regulasi emosi caregiver klien skizofrenia. Kesimpulan: Strategi spiritual care dapat meningkatkan regulasi emosi dan ketenangan dalam bersikap sehingga akan berdampak baik pada proses recovery klien skizofrenia. Kata kunci: anger management; spiritual care; regulasi emosi; caregive; skizofrenia